Classificar o património (re)classificando as identidades. A inscrição do Kola San Jon na lista portuguesa do PCI - Ana Flávia Miguel; Susana Sardo (e-cadernos ces)
In October 2013 the Portuguese Official Gazette published the registration of the performative practice Festa de Kola San Jon, of Cape Verdian origin, in the National Inventory of Intangible Cultural Heritage (PCI). The inclusion of performative practices in the national list of intangible heritage refers, usually, to expressive behaviours associated with the country of registration by attributes of belonging and also to non-discontinued traditions, anchored in the past. In this context, and taking into account the post-colonial profile of the relation between Portugal and Cape Verde, it is important to understand how the classification of Festa de Kola San Jon as Portuguese intangible heritage drives to the reclassification of both Cape Verdian and Portuguese identities. We argue that this procedure is probably a condition to legitimize actions of coexistence, of living together and building a common world among Cape Verdeans, and between Cape Verdeans and the Portuguese. This paper is a draft analysis of three processes: (1) the transplant to Portugal of the performative practice Kola San Jon, (2) how its recontextualization also led to its resignification and, finally, (3) how the patrimony classification is also a way of enabling identity reclassification.